Freedom of Religious Institutions in Society - Shah, Timothy; Berkeley, Nathan A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Religious Freedom Institute's FORIS project, an initiative made possible by funding from the John Templeton Foundation, proudly presents, with the assistance of MDPI, this Special Issue of Religions with a focus on the "Freedom of Religious Institutions in Society." Its strengths lie in its global perspective, the acumen of its authors, and the wide range of subjects and complex factors addressed. This Special Issue volume consists of a series of articles written by leading religious freedom scholars and advocates, including Jonathan Fox, Roger Finke, Paul Marshall, Chad Bauman, Byron Johnson, Timothy Shah, Robert Hefner, Lihui Zhang, Rebecca Supriya Shah, Dane Mataic, Mariz Tadros, and Akram Habib. It contributes to the overall scholarship revolving around religious freedom by placing greater and well-deserved attention upon the crucial nature of institutional religious freedom and its key capacity to enable the enjoyment of religious freedom and human rights in general. Religious liberty is not an individual right alone, but rather includes the right of religious communities to gather in synagogues, churches, mosques, temples, and other houses of worship. Freedom of religion also includes the right of faith communities to establish religious institutions such as schools, hospitals, ministries to the poor, universities, and countless others that seek to embody the teachings of their respective religious traditions. Institutional religious freedom encompasses this full range of congregational and organizational expressions of religious faith.